Comparative Evaluation of Culture Media and pH Conditions for Xylanase Production in Aspergillus niger - Pakaweerachat, Pattarabhorn; Chysirichote, Teerin (My University, 2025)
Xylanase plays a crucial role in the degradation of hemicellulose and holds significant promise across a variety of biotechnological industries. This study investigates the effects of culture medium composition and initial pH on xylanase production by Aspergillus niger. Five different media; Mandels’, Vogel’s, Marciel’s, Okafor’s, and a modified Czapek-Dox, were evaluated for their ability to support enzyme synthesis. Additionally, initial pH levels ranging from 4.0 to 8.0 were tested to identify optimal production conditions. Among the tested media, Mandels’ medium supported the highest xylanase activity, while the optimal pH range for enzyme production was between 6.0 and 7.0. These findings provide valuable insights for optimizing large-scale xylanase production using A. niger, contributing to the development of more efficient and cost-effective bioprocesses. Notably, this study incorporates biomass-specific productivity metrics (IU/g biomass), allowing for a more accurate evaluation of the strain’s enzymatic efficiency. This quantitative approach may help inform future efforts to develop cost-effective and scalable bioprocesses, particularly when applied to low-cost agro-industrial substrates.
Keywords: Biomass-specific Productivity; Culture Medium Optimization; Hemicellulose Degradation; Xylanase